Authority of Amicus Curiae in Constitutional proceedings : Bridging Society and the Constitutional Court - Erlinda Putri Nurdiyanti; Fayza Galih Nur Rohmah; Mahageng Kusumaningtyas; Aris Prio Agus Santoso (West Science Law and Human Rights, 2024)
Amicus Curiae, or friends of the court, is an important instrument in constitutional proceedings in Indonesia even though it does not yet have a standard legal basis. This study discusses the authority of Amicus Curiae in providing additional information, enriching the judge's consideration, and supervising the proceedings of the Constitutional Court. The method used is the literature study approach, which is a research method whose series of research is related to the method of collecting library data, or research whose object of research is studied through various literature information, such as: books, journals, articles and documents. Amicus Curiae is filed in the form of a written document containing legal arguments and other relevant analysis. The Constitutional Court has the authority to reject Amicus Curiae that are judged irrelevant or filed with improper motives. On the other hand, a quality Amicus Curiae can have a positive influence on the decisions of the Constitutional Court and contribute to law enforcement and democracy in Indonesia. Amicus Curiae has not been clearly regulated in Indonesia, but in principle it is accepted under article 5 paragraph 1 of the Law on Judicial Power "Judges and constitutional judges are obliged to explore, follow and understand the legal values and sense of justice that live in society. Furthermore, the confession of the Amicus Curiae can be found in article 180 paragraph 1 of the Code of Criminal Procedure which states that "In the event that it is necessary to clear up the sitting of the matter arising in court, the presiding judge of the trial may request expert testimony and may also request to submit new material by the interested person.